Rule change and Olympic judo scores, penalties and match duration - Calmet, M.; Pierantozzi, E.; Sterkowicz, S.; Challis, B.; Franchini, E. (International Journal of Performance Analysis in Sport, 2017)
In judo, between 2009 and 2013, many changes were added, especially after London 2012 Olympics to promote "positive" actions/score instead of "negative" actions/penalties. This study compared the total match duration, frequency of scores (ippon, wazari, yuko) and penalties (shido) between Rio 2016 and London 2012 (before and after rules change), considering weight categories and competition phases. Data from 470 male athletes and 307 female athletes who disputed, respectively, 1022 and 698 matches in both Olympic Games were analysed. Three-way ANOVA was used to compare sexes, weight categories, Olympic Games edition, with Tukey test as post hoc. The association between Olympic Games edition and percentage of matches without any score was tested via Chi-square and Cramer`s - V effect size was used. Significance level was set at 5%. Eta squared (?2) was used as effect size. Results (Rio 2016 vs. London 2012) suggest in no change in ippon and wazari scores, while decreasing the number of yuko and increasing the number of penalties. Females scored more yuko and received less penalties than males. Females matches in Rio were shorter than matches for all other groups. For scores and penalties, no difference was found concerning weight categories, but half-heavyweight matches were shorter than lightweight ones.